Penelitian Pengaruh Media Sosial Terhadap Etika Anak dan Remaja pada Era Digital - Izzati Nadya; Mariyana Eka Putri; Risma Anita Puriani; Rani Mega Putri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Social media has become an integral part of adolescent activities in the digital age, significantly influencing their ethics and behavior in real life. The widespread use of social media brings various consequences, both positive and negative. Therefore, it is necessary to have a proper understanding and special attention in its use to optimize its benefits and minimize its risks. This study uses a descriptive qualitative approach with a literature review method. The aim of this research is to analyze the impact of social media usage on the ethics of children and adolescents. The findings show negative impacts, such as exposure to content that contradicts social norms, as well as positive impacts, with social media serving as a platform for expanding online social interactions.